Feasibility and evaluation of an emergency department‐based general practitioner streaming and treatment service. Issue 3 (22nd November 2022) - Aldus, Clare; Pope, Ian; Brainard, Julii; Ruston, Annmarie; Hughes, Gareth; Everden, Paul
Abstract: Rationale: Offering a primary care service that can provide good quality primary care at emergency departments may reduce pressure on usual emergency department (ED) services. Aims and Objectives: To evaluate the acceptability, satisfaction, and potential impacts of a co‐located primary care service at an emergency department. Methods: This is a prospective feasibility study and service evaluation comprising a narrative summary of activity, satisfaction, well‐being, and safety, and comparisons of wait times for ED services by patient category ('minor', 'majors', 'paediatric' or 'resus') before and during the service operation. Patients and staff were asked using semistructured interview topic guides about service perception, well‐being, representation within 48 h, safety concerns, and/or satisfaction. Wait times for patient categories in usual ED care service were in secondary care electronic records. Pathway changes were captured under primary care electronic records. Results: Approximately 96% of general practitioner streaming and treatment (GPST) patients were seen within 1 h. There was a statistically significant reduction in ED patients with minor injuries or illnesses waiting >4 h for admission or discharge 'breaches' during the 3 months that GPST was operating compared with the previous 3 months ( p  ≤ 0.005). Wait times for other ED services did not significantly improve. A total of 769 walk‐in patients received GPST consultation and 661 (86%) needed no further ED intervention. Fast discharge was a major determinant of patient satisfaction. No staff expressed dissatisfaction, but some suggested possible improvements in eligibility criteria and built environment design features. Conclusion: Provision of GPST correlated with shorter waits for discharge from ED. Patient and staff experiences of GPST were positive.